Becoming Monolingual: The Impact of Language Ideologies on the Loss of Multilingualism on São Tomé Island - Marie-Eve Bouchard (Languages, 2019)
This article discusses the loss of the creole languages on São Tomé Island and the societal move from multilingualism to monolingualism in Portuguese. It argues that recognizing the ideologies attached to these languages is key in understanding the language shift, but also the processes leading toward monolingualism. This qualitative study is based on three main theories: Language as social practice, language ideology, and monoglot standardization. Data comes from ethnographic fieldwork and sociolinguistic interviews with 56 speakers from the capital of São Tomé and Príncipe. I argue that the existence of multilingualism on São Tomé Island is not valued at a societal level because of the pejorative ideologies that have been held about the creole languages since colonial times. Also, the use of the creole languages stood as a problem for the creation of a unified Santomean nation, as the different racial groups on the islands had their own creole. Results show how ideologies about the Portuguese language and its association with national unity, modernity, and European-ness favored its expansion on São Tomé Island and a move toward monolingualism.